Contemporary Chicana poetry : a critical approach to an emerging literature - Sánchez, Marta Ester (University of California Press, 1985)
Discusses 4 Chicana poets' "dilemmas of their dual relationship to American and Mexican societies and of their dual identity as Chicanas and as women writing in a contemporary setting."